“What’s Going On?”: A Critical Race Theory Perspective on Black Lives Matter and Activism in Education - Dixson, Adrienne D. (Urban education (Beverly Hills, Calif.), 2018)
This article explores activism, education, and the #BlackLivesMatter movement. Using critical race theory (CRT), I analyze what this emergence of primarily youth-led activism means in the context of decades of neoliberal education reform. I raise specific questions about how youth-led activism, which has its genesis in and is largely shaped by social media, not only reflects limited robust mainstream discourses on race but also a failure of education, particularly schools and districts that serve students of color in under-resourced urban communities, to teach about and contextualize other historical movements for justice and racial equity.